Ethno-RSTEM Integrated E-Module Assisted by Virtual Reality to Provide Students with Chemical Literacy and Religious Values - Nurul Fadhilah; Sudarmin Sudarmin; Woro Sumarni (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2026)
This research aimed to describe the characteristics of the e-module containing Ethno-RSTEM assisted by virtual reality, and analyze the feasibility and effectiveness of the e-module to provide students with chemical literacy and religious values. This research method used a 4D model (define, design, develop, disseminate). The instruments in this research consisted of test and non-test instruments. The e-module possessed characteristics in the form of local wisdom content in the city of Kudus, STEM and religious values. The e-module also presented 360-degree videos and Ethno-VR local wisdom of the city of Kudus. The e-module was considered suitable for classroom implementation based on expert evaluations of its content, media, and ethno-virtual reality components. The results of student responses to the e-module in the implementation phase obtained an average score of 68.5 (